Implementing Learner-Centered Lessons to Stimulate Collaborative Learning (2024)
ABSTRACT: This Case Study research aimed at identifying the advantages and disadvantages of implementing Learner-Centered lessons to promote Collaborative Learning. It was carried out in a public school from Medellín in which 25 ninth graders participated. The implementation process lasted 17 weeks of LC lessons containing CL activities. Data collection instruments included teacher’s journals, surveys, a questionnaire and a focus group. Findings revealed LC lessons effectively encouraged CL, especially by fostering students’ agency, peer collaboration, and meaning making. However, differences in group dynamics posed a significant challenge that requires further exploration. Results implied that teachers sharing power with students, what sometimes leads to students overstepping boundaries, should consider other strategies that may help them balance decision making. Results suggest that longer or additional sessions would better support the successful implementation of LC strategies in promoting sustained, high-quality collaboration.